If $\sqrt{a} - \frac{1}{\sqrt{a}} = 1$, then $a + \frac{1}{a} = 3$.

Why this statement is true?

I tried to square the first equation, but it didn't work. I can't understand why there is a 3 in the second equation.


Assuming $a\geq0$, squaring both sides yields $$1=\left(\sqrt{a}-\frac{1}{\sqrt{a}}\right)^2=(\sqrt{a})^2-2\sqrt{a}\frac{1}{\sqrt{a}}+\left(\frac{1}{\sqrt{a}}\right)^2=a-2+\frac{1}{a},$$ and hence $$a+\frac{1}{a}=1+2=3.$$


Squaring the first equation gives:

$(\sqrt{a}-\frac{1}{\sqrt{a}})^2 = 1^2$


$a+\frac{1}{a} = 3$.

Is there a chance you messed up the arithmetic/FOIL somewhere?


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.